Knowledge, Attitudes and Perceptions of Saudis towards Participating in Clinical Trials - AL-Tannir, Mohamad A. (PLoS One, 2016)
AIM: To assess the knowledge, attitudes, and perceptions of Saudis towards participating in clinical trials (CTs). METHODS: A cross-sectional study was conducted on 232 Saudi adult patients and their companions visiting adult outpatient clinics at King Fahad Medical City, Riyadh, Saudi Arabia. Data were collected using a self-administered questionnaire based on information obtained from the literature. The questionnaire was divided into four sections, one covering the respondents’ demographics, and the other three assessing knowledge, attitudes, and perceptions towards participating in CTs. RESULTS: A total of 148 (63.8%) respondents were males, and 52 (22.4%) participants had been invited to participate in a CT previously. Of those, 39 (75%) participated. Knowledge about the essential elements of informed consent ranged from 55.7% (number of participants needed) to 85.7% (confidentiality of personal information). The majority (163, 73.8%) of respondents was willing to participate in a CT after consulting their family physician and 130 (58.0%) respondents would be motivated to participate in a CT if they were healthy. Only 36.8% of the respondents believed that patients who participated in a CT received the best care. Moreover, 110 (48.7%) respondents believed that research was conducted in a responsible and ethical manner. CONCLUSIONS: The present study assessed the current understanding of CTs among Saudi participants. Although the majority of participants had an acceptable level of knowledge about CTs, they exhibited conditional attitudes and misperceptions towards participating in a CT. Increased patient awareness may improve patients’ attitudes towards ethical conduct of CTs.